PPAR-gamma agonist pioglitazone recovers mitochondrial quality control in fibroblasts from PITRM1-deficient patients - Di Donfrancesco, Alessia; Berlingieri, Christian; Giacomello, Marta; Frascarelli, Chiara; Magalhaes Rebelo, Ana Paula; Bindoff, Laurence A.; Reeval, Segel; Renbaum, Paul; Santorelli, Filippo M.; Massaro, Giulia; Viscomi, Carlo; Zeviani, Massimo; et al. (Frontiers in Pharmacology, 2023)
Biallelic variants in PITRM1 are associated with a slowly progressive syndrome characterized by intellectual disability, spinocerebellar ataxia, cognitive decline and psychosis. The pitrilysin metallopeptidase 1 (PITRM1) is a mitochondrial matrix enzyme, which digests diverse oligopeptides, including the mitochondrial targeting sequences (MTS) that are cleaved from proteins imported across the inner mitochondrial membrane by the mitochondrial processing peptidase (MPP). Using fibroblasts derived from patients, we discovered that PITRM1 dysfunction results in the accumulation of MTS, leading to the disruption and dissipation of the mitochondrial membrane potential. This triggers a feedback inhibition of MPP activity, consequently impairing the processing and maturation of imported proteins. Since mitochondrial peptidases also play a role in the maturation of Frataxin, the protein affected in Friedreich's ataxia, we investigated its maturation in patient-derived fibroblasts. Our findings revealed that PITRM1-mutant cells exhibited a significantly lower level of mature Frataxin (mFXN) compared to the control group. Recent studies in yeast indicated that the mitochondrial matrix protease Ste23, which is a homologue of the human insulin-degrading enzyme (IDE), cooperates with Cym1 (homologue of PITRM1) to ensure the proper functioning of the preprotein processing machinery. Although IDE is predominantly located in the cytosol, one isoform localizes to the mitochondrial matrix, where it collaborates with PITRM1 in the digestion of MTS. We found that the pharmacological stimulation of Peroxisome Proliferator-Activated Receptor Gamma (PPARG) by Pioglitazone upregulates IDE and also PITRM1 protein levels restoring the presequence processing machinery and improving Frataxin maturation and mitochondrial function. Our findings provide mechanistic insights and suggest a potential pharmacological strategy for this rare neurodegenerative mitochondrial disease.